2010
DOI: 10.1002/pca.1236
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of microwave accelerated distillation in the extraction of the essential oil of Zygophyllum album L.

Abstract: The MAD method appears to be more efficient than HD: after 30  min extraction time, the obtained yields (i.e. 0.002%) were comparable to those provided by HD after 3  h extraction. MAD seems to be more convenient since the volatile fraction is richer in oxygenated monoterpenes, species that are recognised for their olfactory value and their contribution to the fragrance of the essential oil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
29
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 15 publications
2
29
1
Order By: Relevance
“…Their content is less than 0.5% of the chemical composition in both extracts, although they are best extracted by the HD method. Generally, the microwaveassisted technique gives an extract richer in oxygenated compounds than that obtained by HD [9,11], but in the case of vegetal parts of C. azarolus, the HD oil is richer (61.89%) in oxygenated compounds than the HD-MW oil (41.28%), because a large fraction of both extracts, more than 35% of the volatile constituents, was composed of sesquiterpene hydrocarbons and alkanes. We have already pointed out in our previous works [11,12] that the microwave-assisted technique is very powerful for extracting the latter two families.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Their content is less than 0.5% of the chemical composition in both extracts, although they are best extracted by the HD method. Generally, the microwaveassisted technique gives an extract richer in oxygenated compounds than that obtained by HD [9,11], but in the case of vegetal parts of C. azarolus, the HD oil is richer (61.89%) in oxygenated compounds than the HD-MW oil (41.28%), because a large fraction of both extracts, more than 35% of the volatile constituents, was composed of sesquiterpene hydrocarbons and alkanes. We have already pointed out in our previous works [11,12] that the microwave-assisted technique is very powerful for extracting the latter two families.…”
mentioning
confidence: 99%
“…Essential oil extractions were performed using two different processes, initially by the relatively recent method of hydrodistillation assisted by microwave heating (HD-MW), afterwards by hydrodistillation (HD), the conventional technique recommended by AFNOR in the extraction of essential oils destined for the food and cosmetic industries. Many experiments have been performed in this study in order to optimize the yield of the (HD-MW) extract by studying: (a) the extraction time; (b) the radiation power of the microwave oven; (c) the used quantity of water, starting from a dried distillation, as stated in our previous investigations [9,10]. The extracts were analyzed by gas chromatography GC-FID and gas chromatography coupled to mass spectrometry GC-MS.…”
mentioning
confidence: 99%
“…Essential oil extractions were first performed by the relatively recent technique of hydro-distillation assisted by microwave heating (MAHD) to determine its applicability in the case of leaves and stems of A. clavatus, and then by hydro-distillation (HD) technique, the conventional process recommended by the European pharmacopeia AFNOR in the extraction of edible essential oils. Although microwave heating is an innovative technique, it has been extensively applied in the extraction of natural extracts from vegetal materials and in particular volatile extracts, and has been studied in many papers (22)(23)(24)(25)(26). In order to compare the results produced by both processes, several assays have been carried out to optimize the yield of the MAHD extraction by studying: (i) the level power of microwave radiation; (ii) the extraction time; (iii) the used quantity of water.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, microwave dielectric heating as power source is emerging as safer, more efficient, energy saving, and sustainable extraction process [7]. Reference [8] reported that to provide Zygophyllum album L. essential oil yield of 0.002% using microwave assisted hydrodistillation (MAHD) method required an extraction time of 30 min versus 3 h of hydrodistillation (HD) method. Likewise, reference [6] concluded that microwave steam diffusion (MSDf) for extraction of essential oil from orange peel is clearly advantageous in term of energy and time; the extraction time using MSDf method of 12 min versus 40 min of conventional steam diffusion (SDf) as well as the required energy to perform the two extraction methods are 300 kWh kg -1 essential oil and 120 kWh kg -1 essential oil for SDf and MSDf, respectively.…”
Section: Introductionmentioning
confidence: 99%